Institutional Implications for Stakeholder Modelling: Looking at Institutions in a Centralised Economy - Apostol, Oana; Näsi, Salme (2010)
Originating in the Anglo-American management literature, stakeholder thinking embraces a set of common reasoning and rests on a range of assumptions that pay little attention to the institutional variations across countries and regions with different economic systems. Our aim in this article is to contribute to the stakeholder literature by discussing the significance and implications of this institutional diversity for the stakeholder model.
Keywords: Centralised economy; institutional diversity; stakeholder salience; stakeholder identification; stakeholder model